Management Powertools : A guide to 20 of the most powerful management tools and techniques ever invented - Onsman, Harry (McGraw Hill, 2004)
Covers organisational management and people management tools; presents a wide range of tools in an accessible and useable format; describes every tool objectively and in detail enabling readers to apply it to their workplace. Author has taught and developed programs for a number of Australian universities.